In vivo action of Lactococcus lactis subsp. lactis isolate (R7) with probiotic potential in the stabilization of cancer cells in the colorectal epithelium. (April 2020) - Jaskulski, Itiane Barcellos; Uecker, Julia; Bordini, Fernanda; Moura, Fernanda; Gonçalves, Taiciane; Chaves, Natalie Garcia; Camargo, Flávio; Grecco, Fabiane Borelli; Fiorentini, Ângela Maria; da Silva, Wladimir Padilha; Andreazza, Robson; Pieniz, Simone
Graphical abstract: Highlights: The R7 presented anticancer potential in induced colorectal cancer in animal model. R7 promoted an immune response to the induction of carcinogenic development in animal model. R7 reversed the stress caused by the carcinogenic inducer in animal model. Abstract: Recent research has contributed to advances in the treatment and prevention of colorectal cancer (CRC); however, the prevalence and mortality rate remain high. Lactococcus lactis subps. lactis is commonly used for industrial purposes, but there are no in vivo studies evaluating its anticarcinogenic potential. This study aimed to explore the protective effects of an isolate of L. lactis subsp. lactis (R7) from ricotta on CRC as well as evaluatingbiochemical and hematological parameters resulting from treatment. Wistar rats received subcutaneous doses of 1, 2-dimethylhydrazine (DMH), what is a chemical carcinogen known to induce this carcinogenesis in experimental models, orally a suspension of R7 (10 8 colony-forming units. mL −1 ) and a hypercaloric diet. The results demonstrated a positive effect on the stabilization of the cancer cells induced in the colorectal epithelium, demonstrating anti-carcinogenic potential of R7 against CRC. In addition, an immune response was observed and the biochemical parameters showed that R7 reversed the stress caused by DMH and a hypercaloric diet. The results are promising as regards the behavior of R7 in relation to the treatment of CRC.